Intraempreendedorismo no desenvolvimento de produto de seguro para usinas de a????car e ??lcool. - Brancali??o, Hermes Fernandes (2007)
The intrapreneurship can be defined as the capacity that the employees of an enterprise has, among others, to promove the inovation inside the organization acting as true entrepreneurs, but with a freedom of action a little restrict, because they are not the owners of business. One of the objectives of an intrapreneur action can be conduct the company to reach a profitability above average with this action.The sugarcane alcohol agribusiness turn around R$ 41 billion per year in Brazil, among direct and indirect earnings, what imply in approximately 3,65% of the GNP, besides the fact of Brazil be the biggest sugarcane productor of the world, with more than three hundred factories in activity.Nowadays not so explored for the insurance market, this area has potencial to increment the earnings of an insurance company which get work in a good way the favourable scenary of the increase of global demand for alcohol combustible. Thus, with focus on the Intrapreneurship area, the objective of this research is, given the strategic goals of the studied company, to verify how the prospection of an opportunity can conduct to an intrapreneur action inside an insurance company that explore the sugarcane alcohol area. For attending this objective, it was done a case study, with the identification of strategic factors, intervenient factors, the relationated with the Intrapreneurship, the barriers, the feasibility factors, and the critic points of success.